Analisis Dampak Penerapan IT Service Desk pada Bank XYZ - Prasetyo, Ario Adi; Gaol, Ford Lumban (Bina Nusantara University, 2010)
The purpose of this study is to identify the determinants of IT operational performance related to IT Service Desk. And to determine the consideration of implementing IT Service Desk in the company business processes. The population in this study is 1500 employees or users of the IT Service Desk service. By using the Slovin, 100 users were obtained in the sample. The variables in this study include success factors of IT Service Desk and Problem Management. Methods of data collection include using questionnaire s. Analysis of data is conducted using multivariate analysis of the factor analysis. The conclusions of this research is obtained from, among others, the factors of success of the IT Service Desk and Problem Management. There are 9 to 37 variables and indicators. From the research, it is found that there is a relationship between factors. And after the reduction process of 37 indicators four new factors was formed which consist of a quick solution factor, excellent IT Service Desk factor, focus support factor, and excellent staff factor. From all the new factors, quick solution is the most dominant factor.